THE MERCANTILIST BASIS OF THE INTELLECTUAL LEGACY OF IVAN POSODHKOV - Ya. S. Yadgarov (Финансы: теория и практика, 2017)
The article examines historical preconditions that gave rise to disagreements and disputes regarding the intellectual legacy of one of the prominent Russian economists of the early XVIII century Ivan Pososhkov. Essential aspects of mercantilist and non-mercantilist extracts from his Book of Poverty and Wealth («Kniga o skudosti i bogatstve») are revealed and described.Through a retrospective analysis of past and present alternative assessments of Pososhkov’s economic doctrine it is reasoned that the intellectual legacy of the Russian self-taught economist viewed in the theoretical and methodological context cannot be regarded as belonging to the physiocratism or the classical political economy in the whole, including the institutionalism. It is concluded and proved that Pososhkov’s views are mercantilist in their essence.